A FIGURAÇÃO DA BEBIDA ALCOÓLICA NA OBRA DE TENNESSEE WILLIAMS: MARCAÇÃO SOCIAL, CARACTERIZAÇÃO DE PERSONAGEM E DESLOCAMENTO DO REALISMO - Toledo, Luis Marcio Arnaut de (2024)
The article examines how Tennessee Williams' work portrays characters considered outsiders in American society due to their use of alcoholic beverages. Characters from various plays spanning different phases of his career, both one-acts and full-length works, are identified in this situation, contextualizing their narratives. The study seeks to understand how the use of alcohol identifies these characters as excluded and displaced from society, considering, above all, Linda Dorff’s (1997) concept of character disfigurement, revealing their psychosocial characterization and challenging realism in Williams’ play. In this way, it can be said that Williams constructs these characters to discuss the American Way of Life and the American Dream as capitalist ideologies, presenting characters who are detached from these ideologies.